Hemorrhage and saline resuscitation are associated with epigenetic and proteomic reprogramming in the rat lung. Issue 8 (August 2021) - Bonde, Alexander; Eskesen, Trine G.; Steinmetz, Jacob; Schoof, Erwin M.; Blicher, Lene H.D.; Rasmussen, Lars S.; Sillesen, Martin
Highlights: Trauma and resuscitation are associated with epigenetic modulation Epigenetic modulation includes endothelial and immune activation pathways Trauma-induced epigenetic changes may in part regulate the proteomic response ABSTRACT: Background: Epigenetic changes have been described in trauma patients in the form of histone acetylation events, but whether DNA-methylation occurs remains unknown. We hypothesized that the combination of hemorrhage and saline resuscitation would alter DNA-methylation and associated proteomic profiles in the rat lung. Methods: Ten rats were subjected to a pressure-controlled hemorrhage and resuscitation model consisting of hemorrhage to a mean arterial pressure (MAP) of 35mmHg for 90 minutes, followed by saline resuscitation to a MAP >70mmHg for 90 minutes (n=5) or sham (only anesthesia and cannulation). Lungs were harvested and subjected to reduced genome wide DNA-methylation analysis through bisulphite sequencing as well as proteomics analysis. Data was analyzed for differentially methylated regions and associated alterations in proteomic networks through a weighted correlation network analysis (WCNA). Pathway analysis was used to establish biological relevance of findings. Results: Hemorrhage and saline resuscitation were associated with differential methylation of 353 sites across the genome compared to the sham group. Of these, 30 were localized to gene promoter regions, 31 to exon regions and 87 to intron regions. Network analysis identified an association between hemorrhage/resuscitation and DNA-methylation events located to genes involved in areas of endothelial and immune response signaling. The associated proteomic response was characterized by activations of mRNA processing as well as endothelial Nitric Oxide Synthase (eNOS) metabolism. Conclusion: We demonstrated an association between DNA-methylation and hemorrhage/saline resuscitation. These results suggest a potential role of DNA-methylation in the host response to injury.